Method for in-situ synthesis of Ti-W alloy coated diamond particles, Ti-W alloy coated diamond particles and application of Ti-W alloy coated diamond particles
By synthesising Ti-W alloy in situ to coat diamond particles, the heterocoating, mechanical bonding and graphitization problems existing in the metal layer of diamond abrasive particles in the prior art are solved, and the coating effect with high bonding strength and low cost is achieved.
Patent Information
- Application Number
- CN202411687812.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-25
- Publication Date
- 2025-03-28
AI Technical Summary
The prior art When plating metal layers on diamond abrasive particles, there are problems such as heterogeneous coating, mechanical bonding rather than chemical bonding, prone to cracks in the coating, and excessive plating temperatures leading to diamond graphitization.
The method of synthesizing Ti-W alloy coated diamond particles in situ is used. The diamond particles, titanium hydride powder and tungsten oxide powder are mixed and then cold-pressed, and then heated to 750-950°C under argon or vacuum air atmosphere for diffusion and evaporation coating treatment to form a Ti-W alloy coating layer.
The reaction temperature of Ti-W alloy is reduced, graphitization of diamond surface is avoided, the bonding strength between the plating and diamond is improved, and low-cost, rapid and batch synthesis is achieved.
Smart Images

Figure CN119703070A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of diamond surface-plated metal layers, and in particular relates to a method for in-situ synthesis of Ti-W alloy-coated diamond particles, Ti-W alloy-coated diamond particles and applications thereof. Background Art
[0002] Diamond material has high hardness, high wear resistance, high compressive strength, excellent thermal conductivity and electrical insulation. It has been widely used in diamond saw blades, diamond grinding wheels and diamond drill bits. Due to its series of excellent comprehensive properties, diamond is widely used in many fields of the national economy.
[0003] The bonding force between diamond particles and the matrix is poor, and they are usually mechanically embedded, which is very easy to fall off under the action of grinding force. In order to enhance the bonding force between the metal matrix and the diamond particles, metal is generally plated on its surface at home and abroad, and a stable chemical metallurgical bond is formed between the metal layer and the binder or matrix, thereby improving the quality level of diamond tools.
[0004] At present, there are many methods for coating metal layers on diamond abrasives, including physical vapor deposition (PVD), chemical vapor deposition (CVD), chemical plating, electroplating, microwave heating, spark plasma rapid sintering, etc., but most methods have certain defects in terms of metal or alloy coatings. For example, the gas used in the PVD or CVD method cannot evenly penetrate the bottom of the stacked diamond abrasives, resulting in the formation of heterogeneous coatings on the diamond abrasives. At the same time, the coatings prepared by chemical plating or electroplating are only mechanically bonded to the diamond abrasives, not chemically bonded, which means that these methods cannot prepare carbide coatings. In the process of preparing metal-coated diamonds by spark plasma sintering, due to the fast heating and cooling rates, the thermal stress generated and the difference in the thermal expansion coefficient of the materials cause cracks between the coating and the diamond.
[0005] On the other hand, when the metal coating material reacts with the carbon atoms on the surface of the diamond to form a carbide film (the carbide film can chemically bond the coating to the diamond, and the coating and the diamond have good bonding strength), if the required plating temperature is too high, it is easy to cause excessive erosion and graphitization of the diamond.
[0006] Therefore, it is necessary to provide an improved technical solution to address the above-mentioned deficiencies in the prior art. Summary of the invention
[0007] The object of the present invention is to provide a method for in-situ synthesis of Ti-W alloy coated diamond particles, Ti-W alloy coated diamond particles and applications thereof, so as to help solve or improve the problem of defects in the prior art when plating a metal layer on diamond abrasive particles.
[0008] In order to achieve the above-mentioned object, the present invention provides the following technical scheme: a method for in-situ synthesis of Ti-W alloy coated diamond particles, comprising the following steps: (1) mixing: uniformly mixing diamond particles, titanium hydride powder and tungsten oxide powder to obtain a mixture; (2) cold pressing: cold pressing the mixture obtained by the treatment in step (1) to obtain a cold pressed block; (3) Ti-W alloy plating: heating to 750-950° C. in an argon or vacuum atmosphere, keeping the temperature for 0.5-3 h, and performing diffusion evaporation coating treatment on the cold pressed block; (4) sieving the product obtained by the treatment in step (3), and the sieved material is the Ti-W alloy coated diamond particles.
[0009] Preferably, in step (1), the mass ratio of the diamond particles, titanium hydride powder and tungsten oxide powder is (50-95):(3.75-37.5):(1.25-12.5).
[0010] Preferably, in step (1), the molar ratio of the titanium hydride powder to the tungsten oxide powder is (2.8-3.2):1, and the mass fraction of the diamond particles in the mixture is 50%-95%.
[0011] Preferably, in step (1), the particle size of the titanium hydride powder and / or tungsten oxide powder is less than 50 μm; the particle size of the diamond particles is 40-50 μm; the mixing method is grinding mixing, and after mixing, the step of passing the mixture through a 100-mesh sieve is also included.
[0012] Preferably, in step (2), cold pressing is performed in a cemented carbide mold, and the pressure of the cold pressing is 5-10 MPa.
[0013] Preferably, in step (3), the temperature is first increased to 500°C at a heating rate of 10°C / min, and then increased to 750-950°C at a heating rate of 3-15°C / min.
[0014] The present invention also provides a Ti-W alloy coated diamond particle, which adopts the following technical scheme: a Ti-W alloy coated diamond particle, wherein the Ti-W alloy coated diamond particle is prepared by the method as described above.
[0015] The present invention also provides a diamond tool, which adopts the following technical solution: a diamond tool, wherein components of the diamond tool include the Ti-W alloy coated diamond particles as described above.
[0016] Beneficial effects:
[0017] The in-situ synthesis method of Ti-W alloy coated diamond particles of the present invention helps to reduce the reaction temperature of the Ti-W alloy, avoid or reduce the graphitization of the diamond surface and reduce the strength of the diamond particles. In addition, the in-situ synthesis of the present invention can avoid raw material pollution.
[0018] The method for in-situ synthesis of Ti-W alloy coated diamond particles of the present invention is helpful to realize low-cost, rapid and batch synthesis of Ti-W alloy coated diamond particles. BRIEF DESCRIPTION OF THE DRAWINGS
[0019] The drawings constituting a part of the present application are used to provide a further understanding of the present invention. The exemplary embodiments of the present invention and their descriptions are used to explain the present invention and do not constitute an improper limitation of the present invention. Among them:
[0020] Figure 1 XRD patterns of Ti-W alloy coated diamond particles of Examples 1-4 of the present invention;
[0021] Figure 2 The SEM photographs are of the Ti-W alloy coated diamond particles of Examples 1-4 of the present invention; wherein, (a) is a SEM photograph of the Ti-W alloy coated diamond particles with a mass fraction of 50% of the diamond particles (Example 1); (b) is a SEM photograph of the Ti-W alloy coated diamond particles with a mass fraction of 70% of the diamond particles (Example 2); (c) is a SEM photograph of the Ti-W alloy coated diamond particles with a mass fraction of 90% of the diamond particles (Example 3); (d) is a SEM photograph of the Ti-W alloy coated diamond particles with a mass fraction of 95% of the diamond particles (Example 4);
[0022] Figure 3 The in-situ Raman spectrum of the Ti-W alloy coated diamond particles of the embodiment of the present invention; wherein the four test points in the left figure correspond to different positions of the same diamond particle, and respectively correspond to the spectra with the same number in the right figure;
[0023] Figure 4 The UV spectra of the Ti-W alloy coated diamond particles of Examples 1-4 of the present invention. DETAILED DESCRIPTION
[0024] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. All other embodiments obtained by ordinary technicians in this field based on the embodiments of the present invention belong to the scope of protection of the present invention.
[0025] The present invention will be described in detail below in conjunction with embodiments. It should be noted that the embodiments and features in the embodiments of the present invention can be combined with each other without conflict.
[0026] The present invention aims at at least one of the problems that exist when a metal layer is plated on the surface of diamond particles, namely, it is difficult to achieve chemical bonding between the coating and the diamond (the bonding strength between the diamond particles and the coating is low), cracks are easily formed in the coating, or the plating temperature is too high and the diamond is easily graphitized (the strength of the diamond particles is poor). The present invention provides a method for in-situ synthesis of Ti-W alloy coated diamond particles.
[0027] The method for in-situ synthesis of Ti-W alloy coated diamond particles according to an embodiment of the present invention comprises the following steps: (1) mixing: uniformly mixing diamond particles, titanium hydride powder and tungsten oxide powder to obtain a mixture; (2) cold pressing: cold pressing the mixture obtained by the treatment in step (1) to obtain a cold pressed block; (3) Ti-W alloy plating: heating to 750-950° C. (e.g., 750° C., 800° C., 850° C., 900° C. or 950° C.) under argon or vacuum atmosphere, keeping the temperature for 0.5-3 h (e.g., 0.5 h, 1 h, 1.5 h, 2 h, 2.5 h or 3 h), and performing diffusion evaporation coating treatment on the cold pressed block; (4) sieving the product obtained by the treatment in step (3), and the sieved material is the Ti-W alloy coated diamond particles. Among them, the cold pressing step helps to increase the surface contact area between titanium hydride and tungsten oxide powders and diamond particles, thereby helping to improve their coating effect on diamond particles; in step (3), if the temperature is too low (for example, below 700°C), the reaction cannot take place and the coating of diamond by titanium and tungsten cannot be completed; if the temperature is too high (for example, 1000°C), it is easy to cause graphitization of the diamond surface; if the holding time is too short, the reaction is incomplete; if the holding time is too long, it may cause graphitization of the diamond, affecting the performance of the diamond.
[0028] The inventors found in their research that when titanium and tungsten are plated on the surface of diamond, titanium and tungsten can react with carbon atoms on the surface of diamond under certain conditions to form a carbide film, so that the coating and diamond can be chemically bonded, and the coating and diamond have good bonding strength. However, the plating temperature of tungsten is high (above 1000°C), which can easily cause graphitization of diamond.
[0029] The present invention adopts titanium hydride and tungsten oxide as raw materials, and utilizes titanium hydride (TiH 2) releases hydrogen during the thermal decomposition reaction at 700-1000°C (a continuous process), which can avoid the oxidation or graphitization of diamond (diamond will be oxidized or graphitized when it is in an environment above 800°C, even in an argon atmosphere; the thermal decomposition of titanium hydride under the conditions of the present invention is a continuous process, making the ambient atmosphere a mixed gas of argon and hydrogen, which inhibits the maintenance of diamond), tungsten oxide (WO 3 ) can be H 2 Reduction. Using TiH 2 H released by thermal decomposition 2 Restore WO 3 , Ti-W alloy is obtained, Ti can react with C on the diamond surface at above 600°C to produce TiC, and heat is released locally at the same time, and then the diamond particles are coated with Ti-W alloy by local high temperature diffusion (if titanium or tungsten is plated on the diamond surface separately, the temperature of tungsten plating needs to be above 1000°C, the TiH 2 and WO 3 The W surface generated by the reaction is active and is easier to coat on the diamond surface than elemental tungsten powder; in addition, the reaction is exothermic and can reduce the temperature of the coating system).
[0030] The method of in-situ synthesis of Ti-W alloy coated diamond particles of the present invention helps to reduce the reaction temperature of the Ti-W alloy, avoid or reduce the strength reduction of the diamond particles caused by graphitization of the diamond surface; in addition, under normal circumstances, the temperature of metal W coated diamond needs to be 1000°C (metal W does not react with the diamond surface at 950°C), and the method of the present invention can effectively reduce the temperature of metal W coated diamond compared with the prior art. In addition, the method of in-situ synthesis of Ti-W alloy coated diamond particles of the present invention also helps to avoid raw material contamination (if titanium powder and tungsten powder are used as raw materials, oxides will exist on the surface of the metal element. On the other hand, during the argon atmosphere protection process, the vacuum degree is -0.1Pa, which is not a high vacuum, and there is also trace oxygen. The present method can avoid contamination from the raw materials and the atmosphere).
[0031] In a preferred embodiment of the present invention, in step (1), the mass ratio of diamond particles, titanium hydride powder and tungsten oxide powder is (50-95):(3.75-37.5):(1.25-12.5) (for example, 50:3.75:1.25, 50:3.75:6, 50:3.75:12.5, 50:18:1.25, 50:37.5:1.25, 95:3.75:1.25, 70:3.75:1.25 or 70:15:7, etc.).
[0032] In a preferred embodiment of the present invention, in step (1), the molar ratio of titanium hydride to tungsten oxide is (2.8-3.2):1 (for example, 2.8:1, 2.9:1, 3.0:1, 3.1:1 or 3.2:1), and the mass fraction of diamond particles in the mixture is 50%-95% (for example, 50%, 55%, 60%, 65%, 70%, 75%, 80%, 85% or 95%). When the molar ratio of titanium hydride to tungsten oxide is within the above range, it is conducive to the generation of 3TiH 2 +WO 3 =3Ti+W+3H 2 O reaction, which helps to improve the bonding force between the metal coating and the diamond particles; if the molar ratio of the two is larger or smaller, it will cause theoretically excess titanium hydride or tungsten oxide in the raw material, which is equivalent to using titanium hydride or tungsten oxide alone for diamond surface coating.
[0033] In a preferred embodiment of the present invention, in step (1), the particle size of the titanium hydride powder and / or tungsten oxide powder is less than 50 μm; the particle size of the diamond particles is 40-50 μm; the mixing method can be grinding mixing, and after mixing, the mixture also includes the step of passing the mixture through a 100-mesh sieve (to help avoid powder agglomeration during the mixing process).
[0034] In a preferred embodiment of the present invention, in step (1), the particle size of the titanium hydride powder is less than 325 mesh; the particle size of the tungsten oxide powder is less than 5 μm. If the particle size of the titanium hydride powder and the tungsten oxide powder raw materials is too large, the titanium hydride powder and the tungsten oxide powder can be first mixed and then ground to a suitable particle size (for example, the ball-to-material ratio during ball milling can be (10-20):1, the rotation speed can be 300-500r / min, the time is 2-24h, and the interval is 1-5min; specifically, the ball-to-material ratio can be 10:1, 13:1, 16:1, 19:1 or 20:1; the ball milling speed can be 300r / min, 350r / min, 400r / min, 450r / min or 500r / min; the ball milling time can be 2h, 5h, 10h, 15h, 20h or 24h), and then mixed evenly with the diamond particles (manual mixing). Preferably, after the diamond particles are added, ball milling is not performed in a ball mill jar, so as to help avoid damage to the ball mill jar due to the high hardness of the diamond particles and also help avoid contamination of the sample.
[0035] In a preferred embodiment of the present invention, in step (2), cold pressing is performed in a cemented carbide mold, and the pressure of the cold pressing is 5-10MPa (for example, 5MPa, 6MPa, 7MPa, 8MPa, 9MPa or 10MPa). If the pressure of the cold pressing is too large (greater than 10MPa), the diamond may be crushed, the diamond particle size may be changed, and the strength may also change when the diamond particle size changes, affecting the use of the plated diamond particles; if the pressure is small, the raw materials may not be tightly combined.
[0036] In a preferred embodiment of the present invention, in step (3), the temperature is first raised to 500° C. at a heating rate of 10° C. / min, and then raised to 750-950° C. at a heating rate of 3-15° C. / min (e.g., 3° C. / min, 6° C. / min, 9° C. / min, 12° C. / min or 15° C. / min). The heating rate above 500° C. is 3-15° C. / min, which helps to make the reaction more complete and shorten the holding time at 750-950° C.
[0037] In a preferred embodiment of the present invention, in step (3), after the temperature is raised to 750-950° C., the insulation time is 2-3 h (for example, 2 h, 2.2 h, 2.4 h, 2.6 h, 2.8 h or 3 h).
[0038] In step (4), the aperture of the sieve (Taylor standard sieve) used for screening is smaller than the particle size of the diamond particles in step (1).
[0039] The present invention further provides a Ti-W alloy coated diamond particle. The Ti-W alloy coated diamond particle in the embodiment of the present invention is prepared by the method described above.
[0040] The present invention further provides a diamond tool. The components of the diamond tool in the embodiment of the present invention include the Ti—W alloy coated diamond particles as described above.
[0041] The method for in-situ synthesis of Ti-W alloy coated diamond particles, the Ti-W alloy coated diamond particles and their applications of the present invention are described in detail below through specific embodiments.
[0042] In the following examples: Diamond particles (50-60 μm) were purchased from Henan Tianjian Diamond Industry Co., Ltd.
[0043] Example 1
[0044] The method for in-situ synthesis of Ti-W alloy coated diamond particles in this embodiment comprises the following steps:
[0045] (1) Mixing: Prepare the materials according to the ratio of diamond particle mass: titanium hydride mass: tungsten oxide mass = 50:18.8:31.2 (the molar ratio of titanium hydride to tungsten oxide is 2.8:1); grind and mix the titanium hydride powder (particle size of 40 μm), tungsten oxide powder (particle size of 5 μm) and pretreated diamond particles (particle size of 50-60 μm) in an agate mortar (30 minutes). In order to avoid powder agglomeration during the mixing process, the mixed raw materials are passed through a 100-mesh sieve and sieved three times to make the mixture more uniform.
[0046] (2) Cold pressing: The mixture obtained by the treatment in step (1) is subjected to cold pressing treatment (performed in a cemented carbide mold) at a cold pressing pressure of 5 MPa and maintained at the pressure for 5 minutes.
[0047] (3) Titanium-plated tungsten alloy: The above cold pressed blocks are subjected to diffusion evaporation coating treatment in a rotary atmosphere sintering furnace in an Ar or vacuum atmosphere. The heating process is as follows: first, the temperature is increased from 20°C to 500°C at a heating rate of 10°C / min in the range of 20-500°C; the heating rate from 500°C to the set target temperature is 10°C / min; the target temperature is 800°C, and the holding time after reaching the target temperature is 0.5h.
[0048] (4) Screening: The tungsten-plated sample is separated (screened) using a Taylor standard sieve with a pore size smaller than that of the diamond particles. The material on the sieve is the Ti-W alloy-coated diamond particles of this embodiment (the material under the sieve is the slag after the reaction of titanium hydride powder and tungsten oxide powder).
[0049] Example 2
[0050] The difference between this embodiment and embodiment 1 is that the mass percentage of diamond particles is 70%; the rest is consistent with embodiment 1.
[0051] Example 3
[0052] The difference between this embodiment and embodiment 1 is that the mass percentage of diamond particles is 90%; the rest is consistent with embodiment 1.
[0053] Example 4
[0054] The difference between this embodiment and embodiment 1 is that the mass percentage of diamond particles is 95%; the rest is consistent with embodiment 1.
[0055] Example 5
[0056] The only difference between this embodiment and embodiment 1 is that the mass percentage of diamond particles is 95%; the materials are prepared according to the ratio of diamond particle mass: titanium hydride mass: tungsten oxide mass = 95:1.88:3.12 (the molar ratio of titanium hydride to tungsten oxide is 2.8:1); the target cold pressing pressure in step (2) is 10 MPa; the target temperature in step (3) is 750°C, and the holding time after reaching the target temperature is 3 hours.
[0057] Example 6
[0058] The only difference between this embodiment and embodiment 1 is that the mass percentage of diamond particles is 50%; the materials are prepared according to the ratio of diamond particle mass: titanium hydride mass: tungsten oxide mass = 50:20.4:29.6 (the molar ratio of titanium hydride to tungsten oxide is 3.2:1); the cold pressing pressure in step (2) is 5 MPa; the target temperature in step (3) is 950°C, and the holding time after reaching the target temperature is 0.5h.
[0059] Example 7
[0060] The only difference between this embodiment and embodiment 1 is that the mass percentage of diamond particles is 70%; the materials are prepared according to the ratio of diamond particle mass: titanium hydride mass: tungsten oxide mass = 70:11.3:18.7 (the molar ratio of titanium hydride to tungsten oxide is 2.8:1); the cold pressing pressure in step (2) is 8 MPa; the target temperature in step (3) is 850°C, and the holding time after reaching the target temperature is 1 hour.
[0061] Example 8
[0062] The only difference between this embodiment and embodiment 1 is that the mass percentage of diamond particles is 70%; the materials are prepared according to the ratio of diamond particle mass: titanium hydride mass: tungsten oxide mass = 70:11.8:18.2 (the molar ratio of titanium hydride to tungsten oxide is 3.0:1); the cold pressing pressure in step (2) is 6 MPa; the target temperature in step (3) is 800°C, and the holding time after reaching the target temperature is 0.5h.
[0063] Example 9
[0064] The only difference between this embodiment and embodiment 1 is that the mass percentage of diamond particles is 90%; the materials are prepared according to the ratio of diamond particle mass: titanium hydride mass: tungsten oxide mass = 90:3.8:6.2 (the molar ratio of titanium hydride to tungsten oxide is 2.9:1); the cold pressing pressure in step (2) is 7 MPa; the target temperature in step (3) is 900°C, and the holding time after reaching the target temperature is 0.5 h.
[0065] Example 10
[0066] The only difference between this embodiment and embodiment 1 is that the mass percentage of diamond particles is 80%; the materials are prepared in the ratio of diamond particle mass: titanium hydride mass: tungsten oxide mass = 80:8:12 (the molar ratio of titanium hydride to tungsten oxide is 3.1:1); the cold pressing pressure in step (2) is 9 MPa; the target temperature in step (3) is 900°C, and the holding time after reaching the target temperature is 1 hour.
[0067] Comparative Example 1
[0068] The difference between this comparative example and Example 1 is that the mass ratio of diamond to tungsten powder is 50:50 (only tungsten powder is used to plate the diamond particles); the rest is consistent with Example 1.
[0069] Comparative Example 2
[0070] The difference between this comparative example and Example 1 is that the mass ratio of diamond to titanium powder is 50:50 (only titanium powder is used to plate the diamond particles), and the rest is consistent with Example 1.
[0071] Comparative Example 3
[0072] The only difference between this comparative example and Example 1 is that the target temperature in step (3) is 1050° C.; the rest is consistent with Example 1.
[0073] Comparative Example 4
[0074] The difference between this comparative example and Example 1 is that the mass ratio of diamond particles, titanium hydride powder and tungsten oxide powder is 50:3.3:46.7 (the molar ratio of titanium hydride to tungsten oxide is 0.33:1); the rest is consistent with Example 1.
[0075] Comparative Example 5
[0076] The difference between this comparative example and Example 1 is that the cold pressing pressure is 3 MPa; the rest is consistent with Example 1.
[0077] Experimental example
[0078] 1. Characterization:
[0079] (1) Use X-ray diffractometer to analyze the phase of the plated product and determine the phase structure and composition of the product.
[0080] The XRD patterns of the Ti-W alloy coated diamond particles of Examples 1-4 are as follows: Figure 1 shown.
[0081] from Figure 1The XRD spectrum shows that titanium-coated tungsten diamond is mainly composed of diamond and Ti-W alloy. The diamond ratio in the raw material varies from 50% to 95% without affecting the chemical composition of the titanium-tungsten alloy coating on the surface of diamond particles after sintering. On the one hand, the diffraction peak of the titanium-tungsten alloy indicates that titanium hydride can react with tungsten oxide to form a titanium-tungsten alloy phase; on the other hand, no characteristic peaks of titanium or tungsten oxides are observed, indicating that in-situ chemical reaction coating can avoid the formation of impurity phases.
[0082] (2) The surface morphology of diamond-plated titanium-tungsten alloy was observed using a scanning electron microscope.
[0083] The SEM photos of the Ti-W alloy coated diamond particles of Examples 1-4 are as follows: Figure 2 As shown in the figure, it can be seen that the titanium-tungsten alloy achieves azimuthal coating on the diamond surface, and there is no incomplete coating of corners. The above coating effect is mainly achieved based on three factors: first, the titanium-tungsten content in the ratio of diamond to titanium-tungsten alloy is relatively high; second, the metal activity of the coating combined with titanium hydride dehydrogenation to generate titanium element is high; third, the volatility of tungsten oxide and its reduction reaction with hydrogen drive the movement of titanium-tungsten particles.
[0084] (3) The optical image of diamond and the Raman spectrum of diamond after titanium-tungsten alloy coating were tested using an in-situ laser confocal Raman spectrometer (Renishaw Instruments).
[0085] The in-situ Raman spectrum obtained from the test of the Ti-W alloy coated diamond particles in Example 1 is as follows: Figure 3 shown.
[0086] Depend on Figure 3 It can be seen that the peak of the diamond spectrum line is shifted, which is different from the characteristic peak of diamond measured before coating (1325.8cm -1 ) has a large shift. The shift of the Raman peak before and after coating is caused by the stress between the titanium-tungsten layer and the diamond surface after coating. The Raman spectrum of synthetic Ti-coated diamond particles is at 1580cm -1 There are no characteristic peaks at (G band), indicating that no crystalline graphite is formed on the diamond surface. Figure 3 The four test points correspond to different positions of the same diamond particle. The results of in-situ Raman spectroscopy show that the titanium-tungsten alloy film coated at different positions is uniform.
[0087] (4) Using an FT-IR infrared spectrometer, the UV-visible spectrum of the coated diamond powder is measured between 200-1200 nm.
[0088] The ultraviolet spectra of the Ti-W alloy coated diamond particles of Examples 1-4 are as follows: Figure 4 shown.
[0089] Depend on Figure 4 It can be seen that the ultraviolet absorption spectra of the Ti-W alloy coated diamond particles of Examples 1-4 are similar, with an obvious absorption peak in the 350-450nm wavelength region. In the wavelength region above 600nm, the absorbance of the Ti-W alloy coated diamond particles is significantly increased compared to the uncoated diamond.
[0090] 2. The compressive load and bonding strength of the Ti-W alloy coated diamond particles of Examples 1-10 and the products obtained in the comparative example were tested.
[0091] Test method:
[0092] The particle compressive strength tester measures the compressive load of coated diamond particles. Select a representative sample of coated diamond particles, place a single particle sample on the workbench of the tester with tweezers, and measure the compressive load.
[0093] The multifunctional material surface performance tester measures the bonding strength between the coating layer and the diamond particles.
[0094] The test results are shown in Table 1 below:
[0095] Table 1 Compressive load and bonding strength data of diamond particles and metal coating layers in Examples and Comparative Examples
[0096]
[0097]
[0098] As shown in Table 1, the compressive load of the Ti-W alloy coated diamond particles prepared by Examples 1-10 of the present invention is significantly improved, and the bonding strength between the Ti-W coating layer and the diamond particles is significantly improved compared with the W-plated or Ti-plated diamond particles; TiH 2 , WO 3 The selection of process parameters such as the ratio between titanium and tungsten alloy and diamond particles, cold pressing pressure, sintering temperature and time has a key influence on the performance of titanium-tungsten alloy coated diamond particles.
[0099] In summary, the Ti-W coating was prepared on the surface of diamond particles by diffusion evaporation coating process. Under the conditions of coating temperature of 750-950℃ and holding time of 0.5-3h, the Ti-W coating on the diamond surface was uniform and dense. XRD phase analysis showed that a Ti-W alloy transition layer was formed on the diamond surface. Combined with SEM analysis, different proportions of diamond powder, TiH 2 Pink and WO 3The powder can achieve uniform coating of diamond particles. Raman spectrum shows that the characteristic peak of diamond after Ti-W alloy coating has a large shift. The ultraviolet absorption spectrum of diamond particles coated with Ti-W alloy has an obvious absorption peak at 350-450nm. The above experimental data show that the diffusion evaporation coating process is suitable for mass production in terms of preparation method, and it reduces environmental pollution compared with salt bath coating. In terms of raw material selection, TiH 2 Pink and WO 3 Powder is superior to single metal powder in terms of price and coating effect.
[0100] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.
Claims
1. A method for in-situ synthesis of Ti-W alloy coated diamond particles, characterized in that: The steps include: (1) Mixing: Evenly mixing diamond particles, titanium hydride powder and tungsten oxide powder to obtain a mixture; (2) cold pressing: cold pressing the mixed material obtained by the treatment in step (1) to obtain a cold pressed block; (3) Ti-W alloy coating: in an argon or vacuum atmosphere, the temperature is raised to 750-950° C., and the temperature is kept for 0.5-3 hours to perform diffusion evaporation coating on the cold pressed block; (4) Screening the product obtained by the treatment in step (3), and the material on the screen is the Ti-W alloy coated diamond particles.
2. The method for in-situ synthesis of Ti-W alloy coated diamond particles according to claim 1, characterized in that: In step (1), the mass ratio of the diamond particles, titanium hydride powder and tungsten oxide powder is (50-95):(3.75-37.5):(1.25-12.5).
3. The method for in-situ synthesis of Ti-W alloy coated diamond particles according to claim 2, characterized in that: In step (1), the molar ratio of the titanium hydride powder to the tungsten oxide powder is (2.8-3.2):1, and the mass fraction of the diamond particles in the mixture is 50%-95%.
4. The method for in-situ synthesis of Ti-W alloy coated diamond particles according to claim 1, characterized in that: In step (1), the particle size of the titanium hydride powder and / or tungsten oxide powder is less than 50 μm; The particle size of the diamond particles is 40-50 μm; The mixing method is grinding and mixing, and after mixing, the step of passing the mixed material through a 100-mesh screen is also included.
5. The method for in-situ synthesis of Ti-W alloy coated diamond particles according to claim 1, characterized in that: In step (2), cold pressing is performed in a cemented carbide mold at a pressure of 5-10 MPa.
6. The method for in-situ synthesis of Ti-W alloy coated diamond particles according to claim 1, characterized in that: In step (3), the temperature is first increased to 500°C at a heating rate of 10°C / min, and then increased to 750-950°C at a heating rate of 3-15°C / min.
7. A Ti-W alloy coated diamond particle, characterized in that: The Ti-W alloy coated diamond particles are prepared by the method according to any one of claims 1 to 6.
8. A diamond tool, characterized in that: The component of the diamond tool comprises the Ti—W alloy coated diamond particles as claimed in claim 7.